ACE2 Expression in the Cat and the Tiger Gastrointestinal Tracts - Chiocchetti, Roberto; Galiazzo, Giorgia; Fracassi, Federico; Giancola, Fiorella; Pietra, Marco (Frontiers in Veterinary Science, 2020)
Angiotensin-converting enzyme 2 (ACE2) has been identified as the functional receptor for Severe Acute Respiratory Syndrome—Coronavirus−2 (SARS-CoV-2). It has been identified in the human gastrointestinal tract (GIT), and SARS-CoV-2 has been isolated in human and animal fecal samples. The aim of the present study was to investigate the expression of ACE2 in the gastrointestinal tract of domestic (cat) and wild (tiger) felines. Samples of the pylorus, duodenum, and distal colon were collected from six cats and one tiger. The tissues were processed for immunofluorescence assay with an anti-human ACE2 antibody. Angiotensin-converting enzyme 2 was widely expressed in the gastrointestinal mucosa of the cats and the tiger. In both the species, ACE2-immunoreactivity (ACE2-IR) was expressed by the mucosal epithelial cells of the GIT and by the enteric neurons. In the cats, ACE2-IR was also expressed by the smooth muscle cells of the blood vessels and the tunica muscularis. The expression of the ACE2 receptor in enteric neurons may support the potential neurotropic properties of SARS-CoV-2. Although the evidence of ACE2-IR in the feline GIT does not necessarily indicate the possibility of viral replication and SARS-CoV-2 spread with stool, the findings in the present study could serve as an anatomical basis for additional studies considering the risk of the SARS-CoV-2 fecal-oral transmission between cats/felids, and between cats/felids and humans.